2017
DOI: 10.1242/dev.139949
|View full text |Cite
|
Sign up to set email alerts
|

COUP-TFI mitotically regulates production and migration of dentate granule cells and modulates hippocampal CXCR4 expression

Abstract: Development of the dentate gyrus (DG), the primary gateway for hippocampal inputs, spans embryonic and postnatal stages, and involves complex morphogenetic events. We have previously identified the nuclear receptor COUP-TFI as a novel transcriptional regulator in the postnatal organization and function of the hippocampus. Here, we dissect its role in DG morphogenesis by inactivating it in either granule cell progenitors or granule neurons. Loss of COUP-TFI function in progenitors leads to decreased granule cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…The mouse Nr2f1 and human NR2F1 proteins are very well conserved during evolution and share 98–100% of sequence homology in both DBDs and LBDs (Bertacchi et al , ). Nr2f1 is widely and dynamically expressed in several mouse brain regions (Wang et al , ; Qiu et al , ; Tripodi et al , ; Armentano et al , ; Lodato et al , ; Alfano et al , ; Flore et al , ; Parisot et al , ; Bertacchi et al , ), and its expression pattern seems to be well conserved in human embryos and fetuses, as recently shown (Alzu'bi et al , ,b). Thus, structural and expression similarities between mouse and humans strongly suggest a conserved role of NR2F1 during development of the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The mouse Nr2f1 and human NR2F1 proteins are very well conserved during evolution and share 98–100% of sequence homology in both DBDs and LBDs (Bertacchi et al , ). Nr2f1 is widely and dynamically expressed in several mouse brain regions (Wang et al , ; Qiu et al , ; Tripodi et al , ; Armentano et al , ; Lodato et al , ; Alfano et al , ; Flore et al , ; Parisot et al , ; Bertacchi et al , ), and its expression pattern seems to be well conserved in human embryos and fetuses, as recently shown (Alzu'bi et al , ,b). Thus, structural and expression similarities between mouse and humans strongly suggest a conserved role of NR2F1 during development of the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 78%
“…Since Nr2f1 promotes cell differentiation in different regions of the CNS (Faedo et al, 2008;Lodato et al, 2011a;Parisot et al, 2017;Bertacchi et al, 2018), we asked whether partial or complete loss of Nr2f1 function in the NR would affect cell proliferation and/or RGC differentiation ( Fig 2J-V). Retinal neurons start to be generated around E11.5 in the mouse eye and express the neuron-specific btubulin marker Tuj1 and the RGC marker Brn3a (Heavner & Pevny, 2012).…”
Section: Pre-and Early Postnatal Optic Nerve Defects In Nr2f1 Mutantsmentioning
confidence: 99%
“…COUP-TFI (also called NR2F1) is a nuclear hormone receptor acting as a strong transcriptional regulator whose functions range from the control of embryonic NSC behavior (Naka-Kaneda et al, 2014;Naka et al, 2008) to the regulation of cell migration in the neocortex and developing DG (Alfano et al, 2011;Bertacchi et al, 2018;Parisot et al, 2017). Cortical depletion of COUP-TFI during early stages results in abnormal motor skill behavior and spatial memory deficits (Flore et al, 2016;Tomassy et al, 2010), and haploinsufficiency of COUP-TFI in patients leads to global developmental delay, intellectual disabilities, and optic atrophy (Al-Kateb et al, 2013;Bosch et al, 2014;Bertacchi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which CTR-truncated RELN mediates abnormal positioning of the Cajal-Retzius cells is not obvious. Potential mechanisms involved could be altered CXCR4-CXCL12 signaling (Bagri et al, 2002;Lu et al, 2002;Li et al, 2009;Hodge et al, 2013;Parisot et al, 2017), and an abnormal contact-mediated repulsion, which was shown to be mediated by Eph/ephrin signaling (Villar-Cervino et al, 2013).…”
Section: A Reln Mutation Can Cause Abnormal Positioning Of Cajal-retzmentioning
confidence: 99%